Therapeutic potential of anti-thymocyte globulin in type 1 diabetes: A systematic review - Rahul Mittal; Keelin McKenna; Joana R. N. Lemos; Shreya Juneja; Mannat Mittal; Khemraj Hirani (PLoS ONE, 2025)
Background Type 1 diabetes (T1D) is an autoimmune condition characterized by the destruction of insulin-producing beta cells in the pancreas. Anti-Thymocyte Globulin (ATG) has emerged as a promising immunomodulatory therapy aimed at preserving beta-cell function and altering the disease course. This systematic review synthesizes current evidence from the clinical trials evaluating the efficacy and safety of low-dose ATG in individuals with T1D. Methods We conducted a comprehensive literature search of electronic databases, including PubMed (MEDLINE), Science Direct, Scopus, EMBASE, and ClinicalTrials.gov, to identify studies investigating ATG in T1D in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. The Joanna Briggs Institute (JBI) Critical Appraisal Tools for randomized clinical trials and case-control studies were used to assess the quality and evaluate the risk of bias in the eligible studies. Results The primary outcomes assessed were preservation of C-peptide levels, glycemic control, and adverse events. Results indicated that ATG showed potential in preserving beta-cell function and improving clinical outcomes in recent-onset T1D. However, the incidence of adverse events, such as cytokine release syndrome and lymphopenia, necessitated careful monitoring and management. Conclusion Low-dose ATG presents a promising therapeutic approach for modifying the progression of T1D. While early-phase trials demonstrate potential benefits in preserving beta-cell function, further large-scale, long-term studies are essential to establish optimal dosing regimens, long-term efficacy, and safety profiles. This review highlights the importance of continued research to fully elucidate the role of ATG in T1D management.